COMPETENCY, COLLABORATION, MOTIVATION AND WORK DISCIPLINE OPERATION ON THE PERFORMANCE OF THE ROOM NURSE AT ORTHOPEDIC PROF DR.R.SOEHARSO HOSPITAL SURAKARTA - Tri Budi Santoso; Sarsono Sarsono; Istiatin Istiatin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research evaluates the impact on the operating room nurse's efficiency at Prof. Dr R. Soeharso Orthopedic Hospital, Surakarta, of competence, teamwork, encouragement, and work discipline. This research method using quantitative descriptive. The population of all nurses who work at Orthopedic Hospital Prof. Dr R. Soeharso Surakarta, totalling 180 people. The sampling technique used in this study was the purposive sampling technique with the number of samples in the study were 45 people or respondents. Data collection using a questionnaire. The data analysis technique used is multiple linear regression test, model feasibility test, hypothesis test, and determination coefficient. The results showed that competence, collaboration, motivation, and work discipline affected the operating room nurse's performance at Prof. Dr R. Soeharso Orthopedic Hospital, Surakarta. The variable shows that competence, collaboration, motivation, and work discipline affect nurses' performance by 0.825 or 82.5%, while 17.5% are influenced by other variables that are not studied, such as work environment, ability, education, and others. Suggestions from this study, Prof. Dr R. Soeharso Surakarta Orthopedic Hospital continues to improve the quality of existing competencies, collaboration, motivation, and work discipline, so that nurses' performance will increase and become better than before.